DEVELOPMENT AND DISTRIBUTION OF NATIONAL SPORTS IN UZBEKISTAN - Ilal Najimov (Proximus Journal Publishing, 2024)
The article is devoted to the development and spread of national sports in Uzbekistan. It highlights the state policy regarding the preservation and popularization of national sports and folk games, which are held regularly and everywhere in order to attract the population, especially young people.
Keywords: Youth; sports; sports games; national sports